Donati inducted into Hall (Raton Range Raton, New Mexico, 1990)
Article on Lois Donati being inducted into the Democratic Hall of fame.
Master list item #: 39
File location is in the Raton File Cabinet
Keywords: Donati, Lois; Powell, Ray; Campbell, Jack; Rojas, Louis; Gutierrez, Dan; Trujillo, Miguel; Chavez, Dennis; Lopez, Lucy; Montoya, Joseph M; Ferguson, Columbus; Miera, Ruben; Rubenstein, Jules; Baca, Delphine; Naranjo, Emilio; Hopper, Joe; Martinez, Walter; Fowler, Vasti; Brown, Polk; El Dorado; Local History; Biography; Hall of Fame; Democratic Party; Raton, New Mexico; Santa Fe, New Mexico